An Analysis of Students’ Problems in Writing Procedure Text at The Tenth Grade Students of SMA Negeri 1 Sepang - Elicia Citra Dewi; Tampung N. Saman; Ristati (The Study Program of English Education of Palangka Raya University, 2023)
Writing is one of the basic English language abilities that should be mastered by English Learners. However, many Indonesian students, especially at the High School level, face difficulties in writing. Evidently, in the context of this study was conducted to find out students’ abilities and to explore the main problems faced by students in writing procedure texts. The method of this research was descriptive qualitative research. The sample of this research was 29 students of class X IPA2 at SMA Negeri 1 Sepang. Form of writing procedure text was used as the instrument to collect the data and a documentation technique was applied to collect the data. Afterward, the data were analyzed with a rubric analytical scale by brown (2007). The result showed that 13,8% of students were in a very good level, 17.2% of students in a good level, 17.2% of students in a fair level, and 51.6% of students were in a poor level. Therefore, 24.1% of students are classified in the poor level of language features category which means, language features are the most difficult area faced by the tenth-grade students of SMA Negeri 1 Sepang with the number frequency 24.1% students in a poor level.